Relevance of diet in schizophrenia: a review focusing on prenatal nutritional deficiency, obesity, oxidative stress and inflammation - Rarinca, Viorica; Vasile, Amalia; Visternicu, Malina; Burlui, Vasile; Halitchi, Gabriela; Ciobica, Alin; Singeap, Ana-Maria; Dobrin, Romeo; Burlui, Ecaterina; Maftei, Lucian; Trifan, Anca (Frontiers in Nutrition, 2024)
Background/ObjectivesSchizophrenia is a complex mental disorder influenced by genetic and environmental factors, including dietary habits. Oxidative stress and inflammation play a crucial role in the pathophysiology of schizophrenia. Emerging research suggests that diet may affect schizophrenia through different biological mechanisms beyond oxidative stress and inflammation. In particular, epigenetic changes may alter the expression of genes related to neurodevelopment and neurotransmitter systems, while neuroplasticity plays a crucial role in brain adaptation and resilience to psychiatric disorders.MethodsThe literature search included the main available databases (Science Direct, PubMed and Google Scholar), considering the English language, and our screening was performed based on several words such as “schizophrenia”, “diet”, “nutrients”, “obesity”, “oxidative stress”, “inflammation”, “antioxidants” and “prenatal nutritional deficiency”. The review focused specifically on studies examining the relevance of diet in schizophrenia, as well as prenatal nutritional deficiency, obesity, oxidative stress, and inflammation associated with this disorder.ResultsFollowing a review of the literature, it was found that nutritional deficiencies, including lack of omega-3 fatty acids, vitamins D, and B, during the prenatal and postnatal periods can have a negative impact on neurodevelopment and increase the risk of schizophrenia. Patients with schizophrenia have imbalances in antioxidant enzymes, such as glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT), and reduced levels of antioxidants (vitamin E, vitamin C). These biochemical changes lead to an increase in markers of oxidative stress, including malondialdehyde (MDA). In addition, cytokine-mediated inflammation, microglial activation, and intestinal dysbiosis are associated with the onset of schizophrenia and the severity of schizophrenia symptoms. Currently, there is no universally accepted dietary regimen for control. However, various diets and nutritional methods are being researched and applied to alleviate the symptoms of schizophrenia and improve the overall health of patients, including the Mediterranean diet, the ketogenic diet, the gluten-free diet, and the DASH (Dietary Approaches to Stop Hypertension) diet.ConclusionA healthy diet, rich in anti-inflammatory nutrients and antioxidants, may help manage schizophrenia by reducing oxidative stress, preventing complications, and improving quality of life. Omega-3 fatty acids, vitamin D, and B vitamins are particularly important for brain development and function. In this review, we aim to analyze the literature on the influence of diet on schizophrenia, focusing on the role of prenatal nutritional deficiencies, obesity, oxidative stress, and inflammation.